(untitled) (Scientific journal of the Fergana State University, 2024)
Support 10% SE, Alphasav 20% SE, Killer Extra 10% SE, Entovant PRO 30% SE, Emamek, 5.7% WDC., Surrender, 5% SE. One of the main goals of the experiment is to study the effectiveness of using chemicals against cotton bollworm.